Blood blueprint of cricket players: exploring variations in hematological parameters based on playing roles - Shaybal Chanda; Hozzatul Arafeen Sujon; Farjana Akter Boby; Carmen Magdalena Camenidis; Vlad Adrian Geantă (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Background: Cricket is an outdoor sport where players, including batsmen, bowlers, and all-rounders, encounter various physical challenges and demands. Complete Blood Count (CBC) is an essential test for understanding hematological parameters, playing a crucial role in monitoring overall health detecting deficiencies like iron deficiency or anemia, assessing recovery, and optimizing athletic performance.